Bis(2-Ethylhexyl) Terephthalate from Olax Imbricata, Natural Substance or Artifact? - Nguyen, Thi Bich Tram; Nguyen, Linh Nham; Vo, Thi Nga (Journal of Technical Education Science, 2023)
The medicinal plant Olax imbricata is well-known for its antioxidant, anti-inflammatory, antibacterial, and diabetes-treating properties. It is essential to investigate the chemical composition and biological activity of Olax imbricata. During our investigation of this plant, a terephthalate derivative, bis(2-ethylhexyl)terephthalate, was isolated from methanol extract using chromatographic techniques and elucidated using nuclear magnetic resonance spectroscopy. Terephthalate’s presence in Olax imbricata has raised concerns regarding whether or not it is a natural substance or an artifact. It is challenging to persuade others that bis(2-ethylhexyl)terephthalate isolated from Olax imbricata is the biosynthetic compound produced by this medicinal plant. Sequestration of bis(2-ethylhexyl)terephthalate from Olax imbricata may be the result of laboratory equipment, adsorbents, and solvents used during extraction or isolation. This finding cautions laboratory staff when using plastic utensils exposed to organic solvents. A sign identifying bis(2-ethylhexyl)terephthalate is silica gel thin layer-chromatography performance eluting with n-hexane : ethyl acetate (96:4). A dark spot appears at Rf 0.46 under ultra-violet light at 254 nm or as a steel blue spot when stained with a solution containing 1% vanillin and 10% H2SO4 in ethanol.